2009
DOI: 10.1021/nn900084e
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically Nanostructured Rutile Arrays: Acid Vapor Oxidation Growth and Tunable Morphologies

Abstract: A general acid vapor oxidation (AVO) strategy has been developed to grow highly oriented hierarchically structured rutile TiO(2) nanoarrays with tunable morphologies from titanium thin films. This is a simple one-pot synthesis approach involving the reaction of a titanium surface with the vapor generated from a hydrochloric acid solution in a Teflon lined autoclave. To the best of our knowledge, this is the first successful attempt to grow ordered tree-like titania nanoarrays. A possible formation mechanism fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
90
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(92 citation statements)
references
References 51 publications
(102 reference statements)
2
90
0
Order By: Relevance
“…However, these nanostructures have a low dye adsorption and hence small light harvesting efficiency because of large number of gaps existing among the wires. Yang et al [22] synthesized treelike TiO 2 nanoarrays on metal Ti foils but their application in DSSCs was limited [23] fabricated treelike TiO 2 nanostructures on SnO 2 via pulsed laser deposition for photoanodes in DSSCs and achieved a good light-to-electricity conversion efficiency. However, compare to vapor phase techniques, solutionbased methods are more appropriate for low cost mass production.…”
Section: Introductionmentioning
confidence: 99%
“…However, these nanostructures have a low dye adsorption and hence small light harvesting efficiency because of large number of gaps existing among the wires. Yang et al [22] synthesized treelike TiO 2 nanoarrays on metal Ti foils but their application in DSSCs was limited [23] fabricated treelike TiO 2 nanostructures on SnO 2 via pulsed laser deposition for photoanodes in DSSCs and achieved a good light-to-electricity conversion efficiency. However, compare to vapor phase techniques, solutionbased methods are more appropriate for low cost mass production.…”
Section: Introductionmentioning
confidence: 99%
“…Since Kasuga reported the hydrothermal synthesis of titanate nanotubes [13], morphology-controlled titanate nanostructures, such as nanotubes [4,14], nanosheets [15,16] and nanorods [17], have been considerably explored. Particularly, many interesting nanostructures can be obtained by vapor-solid-liquid interface-controlled methods [18][19][20]. For example, Yang et al reported that hierarchically structured TiO 2 nanoarrays with tunable morphologies are synthesized via a general acid vapor oxidation strategy at the vapor-solid interface [19].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, many interesting nanostructures can be obtained by vapor-solid-liquid interface-controlled methods [18][19][20]. For example, Yang et al reported that hierarchically structured TiO 2 nanoarrays with tunable morphologies are synthesized via a general acid vapor oxidation strategy at the vapor-solid interface [19]. It has also been reported that thin films of metals, metal chalcogenides and oxides can be prepared by interfacial deposition schemes, and that the structural properties of the deposits, such as grain size and morphology, can be controlled by the reaction parameters [20].…”
Section: Introductionmentioning
confidence: 99%
“…Park et al synthesized rutile TiO 2 nanobranches using a seeding method with TiO 2 nanowires as a seed [58]. Wu et al reported the assembly of rutile nanotree, nanoflower, and cross-medal arrays through a simple acid vapor oxidation (AVO) [59][60][61]. Despite these advances, the range of rutile TiO 2 geometries still needs to be expanded to meet the increasing nano-and microtechnological demands.…”
Section: Introductionmentioning
confidence: 99%